AES Algorithm for the Next Generation of 5G Network Encryption Standards - T, Manojkumar; K, Tamilarasi; S, Mahalakshmi; P, Vinayagam; U, Mahanthesha; S, Mohanraj (2023 International Conference on Advances in Computing, Communication and Applied Informatics (ACCAI), 2023)
The Advanced Encryption Standard (AES) symmetric key encryption algorithm is the industry standard for 5G communication encryption. Technology advancements nowadays are mostly aimed at improving the security, speed, and efficiency of processors. The main expansion phase is made easier by the study's pipeline structure. This method simplifies the process of creating subkeys in AES encryption for use in 5G communication networks. There is a 37% increase in throughput between the simulated and implemented versions of the original design on FPGA Virtex4 XC4VLX200, and this difference may be attributed to the reduction in propagation latency while producing subkeys.